PENGARUH RENDAM KAKI DENGAN AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI KELURAHAN GAHARU - Lasma Rina Efrina Sinurat; Siska Dwi Ningsih; Henny Syapitri (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Hypertension is an increase in diastolic and systolic blood pressure that is intermittent or persistent. The national prevalence of hypertension at the age of 55-64 years is 45.9%, those aged 65 years and over are 57.6%, and those aged 75 years and over are 63.8%. One of the complementary alternative therapies in hypertensive patients is doing